ANALISIS STRATEGI PEMASARAN DIGITAL MELALUI MEDIA SOSIAL TIK TOK DALAM MENINGKATKAN PENJUALAN PRODUK ONLINE SHOP - Anindya Prastiwi Setiawati; Budi Andreanto (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
The aim of this research is to analyze digital marketing strategies through TikTok social media in increasing sales of online shop products at ETHICA.official Surabaya. This research is field research with a qualitative descriptive approach, the data used is primary data and secondary data. With data collection techniques in the form of interviews, observation, questionnaires and documentation. The population used was 6 ETHICA.official Surabaya managers. and the sample to see consumer responses was 47 people with indicators of respondents who had made purchases in the last month. The results of this research are advertising using Tik Tok social media, sales promotions using discounts or price reductions, premiums or gifts, trade shows, coupons or vouchers, and product guarantees. Publicity in the form of the SFS (shotout for shotout) community and also cross-promotion between fellow online shop businesses. With this concept, ETHICA.official Surabaya's sales are able to increase every year. The promotional activities carried out by ETHICA.official Surabaya are also appropriate so that consumers do not need to be afraid of being deceived in transactions with ETHICA.official Surabaya because the basic business of ETHICA.official Surabaya is an online shop because of the availability of the ETHICA.official Surabaya store. Turi Market, 3rd Floor Surabaya, Surabaya City, East Java. Apart from that, the sales implementation of ETHICA.official Surabaya is honest and avoids false promotions, does not hide defects in goods and keeps promises.